Artificial intelligence and suicide prevention: A systematic review - Alban Lejeune; Aziliz Le Glaz; Pierre-Antoine Perron; Johan Sebti; Enrique Baca-Garcia; Michel Walter; Christophe Lemey; Sofian Berrouiguet (European Psychiatry, 2022)
Abstract